Liberal professions and illiberal politics Hungary from the Habsburgs to the Holocaust - Kovács, Mária M. (Woodrow Wilson Center Press u.a., 1994)
In this important new historical survey of social and intellectual history, Maria Kovacs examines the struggle between liberal and anti-Semitic policies in professional groups - doctors, lawyers, engineers - in Hungary up to 1945. Kovacs's main emphasis is on the interwar period when unemployment, expansion of the welfare system, and competition for state jobs during the Great Depression, combined with crass anti-Semitism on the part of engineers, and medical associations, radically altered previously liberal policies of open entry and equal educational opportunity. Liberal Professions and Illiberal Politics uses extensive archival records to assess to what extent these new policies were dictated by authoritarian governments from above and to what extent they originated within the professions themselves. The story ends with the Holocaust, which sealed the fate of those professionals who had become victims of persecution under the German occupation of Hungary. This fascinating analysis, a copublication with the Woodrow Wilson Center Press, will be of interest not only to scholars and students of Jewish history but also to the general reader interested in a case study of ethnic segregation within the learned professions.
Keywords: Geschichte 1850-1939; Geschichte 1900-1945; Academici; Antisemitisme; Beroepsorganisaties; Liberalisme; Uitsluiting; Professional socialization -- Hungary; Professions -- Sociological aspects; Liberalismus; Akademiker; Politisches Denken; Antisemitismus; Berufsverband; Ungarn; Hungary -- Social conditions